Standardization of Sterilization Protocol for Nodal and Leaf Explants of Field Grown Mature Tree of Diploknema butyracea - Kunwar, Arti; Thakur, Ajay (Indian Forester, 2017)
Standardization of sterilization is the most important step to establish aseptic culture. Experiments were carried out for disinfection of two types of explants; nodal and leaf, taken from mature tree of Diploknema butyracea. Explants were presterilized with an aqueous solution of bavistin (Carbendazim) 0.1-2.0 % for 3-15 minutes. Among all the sterilizing agents viz; HgCl2, NaOCl and H2O2, preeminent result for nodal explant was obtained in 0.2 % HgCl2 for 15 minutes and for leaf explants treatment with 0.1 % HgCl for 5 minutes was found to be the best.